Changes in the bilateral pulse transit time difference with a moving arm - Jiang, Xinge (Technol Health Care, 2018)
BACKGROUND: Changes of pulse transit time (PTT) induced by arm position were studied for unilateral arm. However, consistency of the PTT changes was not validated for both arm sides. OBJECTIVE: We aimed to quantify the PTT changes between horizontal and non-horizontal positions from right arm and left arm in order to explore the consistency of both arms. METHODS: Twenty-four normal subjects aged between 21 and 50 (14 male and 10 female) years were enrolled. Left and right radial artery pulses were synchronously recorded from 24 healthy subjects with one arm (left or right) at five angles (90 [Formula: see text] , 45 [Formula: see text] , 0 [Formula: see text] , [Formula: see text] 45 [Formula: see text] and [Formula: see text] 90 [Formula: see text]) and the other arm at the horizontal level (0 [Formula: see text]) for reference. RESULTS: The overall mean PTT changes at the five angles (from 90 [Formula: see text] to [Formula: see text] 90 [Formula: see text]) in the left arm (right as reference) were 16.1, 12.3, [Formula: see text] 0.5, [Formula: see text] 2.5 and [Formula: see text] 2.6 ms, respectively, and in the right arm (left as reference) were 18.0, 12.6, 1.6, [Formula: see text] 1.6 and [Formula: see text] 2.0 ms, respectively. CONCLUSIONS: Obvious differences were not found in the PTT changes between the two arms (left arm moving or right arm moving) under each of the five different positions (all [Formula: see text] 0.05).